Phosphorus sorption capacity of biochars from different waste woods and bamboo. Issue 2 (28th January 2019) - Li, Yingxue; Xu, Defu; Guan, Yidong; Yu, Kewei; Wang, Wenhua
Abstract: Four biochars were made via pyrolysis at 500 °C using different waste plant materials, including tree branches from Cinnamonum campora (L.) Pres (CCP), Eriobotrya japonica (Thunb.) Lindl (EJL), Rohdea roth (RR) and bamboo shoots ( Phyllostachys sulphurea ) (PS). Phosphorus sorption capacities of the biochars were studied by isothermal experiments on their sorption kinetics. Results show that P sorption to the three wood biochars (CCP, EJL, and RR) fitted well with Lagergren pseudo second order model. However, P release was found in the PS biochar and sand amended with the PS biochar treatments during the isothermal sorption experiment. Phosphorus sorption capacity of the CCP biochar, EJL biochar and RR biochar was 4, 762.0, 2, 439.0 and 1, 639.3 mg/kg, respectively. The CCP biochar showed the highest P sorption capacity due to its higher pH, lower dissolved P content, larger surface area (23.067 m 2 /g) and pore volume (0.058 cm 3 /g). The PS biochar showed the lowest P sorption due to its higher dissolved P content, more carboxyl groups, and smaller surface area (2.982 m 2 /g) and pore volume (0.017 cm 3 /g). Results suggest that the CCP biochar could be a potential alternative adsorbent for P sorption, such as removing P in wastewater treatment by constructed wetlands.